Determinar Estrategias Para La Administración De Riesgos Laborales Y Su Impacto En La Competitividad De Las Empresas - Juárez Cerros, Carlos Alfredo; Bribiescas Silva, Francisco Arturo (European Scientific Journal, ESJ, 2016)
To be a competitive company, it’s necessary that the quality has a high sense of importance for managers; some indicators such as market impact, the gradual increase in the interest of the academic community, the changes in its principles and practices and the organization of experts in the field, show the progress of this topic in organizations. Companies seek management systems that can be easily implemented, and in turn manage them effectively according to their different activities to achieve remain in an increasingly competitive environment; the key to effectively manage quality and risk prevention, is how to meet regulatory requirements and increasingly demanding needs of its main audiences: customers, society and workers, and at the same time allow them to be competitive. In this paper some authors suggest a number of tools for managing occupational hazards that can be used in any business, in order to identify different analysis methodologies and risk controls, based on them are consulted, develop a process that contributes to the continuous improvement of working environments for workers; it is also necessary to implement surveys in the manufacturing sector to corroborate the impact of occupational risk management in the competitiveness of enterprises.